A case of pure autotopagnosia following Creutzfeldt–Jakob disease. Issue 7 (16th November 2016) - Tamura, Itaru; Hamada, Shinsuke; Soma, Hiroyuki; Moriwaka, Fumio; Tashiro, Kunio
ABSTRACT: A 69-year-old male (N.A.) with Creutzfeldt–Jakob disease showed pure autotopagnosia. We administered tests evaluating his ability to name his own body parts, to point to body parts (his own and examiner's), and to recognize positional relationships between his body parts by verbal questions and responses. We found impaired localization of the patient's own body parts by pointing and impaired recognition of positional relationships between his body parts. However, there was no impairment in naming his own body parts or in localizing the examiner's body parts. The results suggest a pure autotopagnosia in N.A. leading to an impairment of recognition of the spatial position of his body parts in a three-dimensional body representation within the egocentric reference frame. We were able to rule out the possibility that his pattern of performance could have been due to a disability in programming reaching movements of the arm.